Love of Money, Machiavellian, Religiusitas dan Kinerja Auditor - Utami Dewi, Ida Ayu Chintya; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 30 No 12 (2020)DO - 10.24843/EJA.2020.v30.i12.p01, 2020)
This study aims to determine the effect of love of money, machiavellian, religiosity on auditor performance. The population in this study were auditors working at the Public Accountant Firm in Bali which were listed in the Indonesia Public Accountants Institute Directory in 2019 so that a sample of 109 auditors was obtained using the technique of determining saturated sample data. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that love of money and machiavellian have a negative influence on the performance of auditors in public accounting firms in Bali and religiosity has a positive effect on auditor performance in public accounting firms in Bali. This research can provide information about love of money, machiavellian, religiosity on the performance of auditors of Public Accounting Firms in Bali, because it can affect the auditor's performance in achieving better work results. Keywords: Love Of Money; Machiavellian; Religiosity.